Accuracy of clinical diagnosis in tremulous parkinsonian patients: a blinded video study. Issue 11 (14th June 2010) - Bajaj, Nin P S; Gontu, Vamsi; Birchall, James; Patterson, James; Grosset, Donald G; Lees, Andrew J
Abstract : Background: This study examines the clinical accuracy of movement disorder specialists in distinguishing tremor dominant Parkinson's disease (TDPD) from other tremulous movement disorders by the use of standardised patient videos. Patients and methods: Two movement disorder specialists were asked to distinguish TDPD from patients with atypical tremor and dystonic tremor, who had no evidence of presynaptic dopaminergic deficit (subjects without evidence of dopaminergic deficit (SWEDDs)) according to 123 I-N-ω-fluoro-propyl- 2β-carbomethoxy-3β-(4-iodophenyl) nortropane ([ 123 I] FP-CIT) single photon emission computed tomography (SPECT), by 'blinded' video analysis in 38 patients. A diagnosis of parkinsonism was made if the step 1 criteria of the Queen Square Brain Bank criteria for Parkinson's disease were fulfilled. The reviewer diagnosis was compared with the working clinical diagnosis drawn from the medical history, SPECT scan result, long term follow-up and in some cases the known response to dopaminergic medications. This comparison allowed a calculation for false positive and false negative rate of diagnosis of PD. Results: High false positive (17.4-26.1%) and negative (6.7-20%) rates were found for the diagnosis of PD. The diagnostic distinction of TDPD from dystonic tremor was reduced by the presence of dystonic features in treated and untreated PD patients. Conclusion: Clinical distinction of TDPD from atypical tremor, monosymptomatic rest tremor and dystonic tremor can be difficult due to the presence of parkinsonian features in tremulous SWEDD patients. The diagnosis of bradykinesia was particularly challenging. This study highlights the difficulty of differentiation of some cases of SWEDD from PD.